The Role of Logic in Understanding Truth in the Educational Environment - Inayah, Inayah; Affandi, Akhmad; Ali, Moh; Hidayat, Ade (Journal of English Language and Education, 2026)
This research explores the role of logic in the understanding of truth in educational settings, using a hermeneutical-philosophical approach. Logic, as a rational thinking tool, serves to develop students' critical and analytical thinking abilities, while science, through empirical methods, provides an evidence-based framework that supports the understanding of truth. However, the application of logic is often limited to theoretical aspects without a practical context, and science education tends to emphasise memorisation over process exploration. This paper proposes the integration of logic and science through an integrated curriculum, project-based approaches and the use of technology to create a holistic education that supports students' character and critical reasoning. This integration creates harmony between rationality and local values, relevant for 21st century education that respects cultural diversity. This research highlights the challenges of creating an inclusive yet value-based education and offers practical recommendations to improve the relevance of logic in learning.